Perbandingan Dosis Warfarin terhadap Durasi Tercapainya Target INR pada Pasien CHF dengan Fibrilasi Atrial - Tiara Tri Agustini; Helmi Arifin; Akmal M. Hanif (Jurnal Sains Farmasi & Klinis, 2016)
A study of comparison between warfarin dose with achieving target INR in patients with CHF and atrial fibrillation at RSUP. DR. M. Djamil Padang has been investigated. This study analyzed using one-way ANOVA and if the result is significant then followed by post hoc test. Of the total 27 patients, all the patients suffering from CHF and 11 patients suffering from hypertension. There were 15 patients aged <60 years, 11 patients aged between 60-74 years, and 1 patient aged ≥75 years. The number male and female patients are 11 and 16 people. The mean duration of achieving the target INR at dose 2 mg, dose (2 mg and 4 mg) and dose 5 mg are 38.22, 29.33, and 6.56 days. There is a significant difference in the mean duration of achieving the target INR in the dose group. 5 mg dose had a mean duration of achieving the target INR which significantly different compared to the other doses. A study of comparison betweenwarfarin dose with achieving target INR in patients with CHF and atrial fibrillation at RSUP. DR. M. Djamil Padang has been investigated. This study analyzed using one-way ANOVA and if the result is significant then followed by post hoc test. Of the total 27 patients,all the patients suffering fromCHF and11 patients suffering from hypertension. There were 15 patients aged <60 years, 11 patients aged between 60-74 years, and 1 patient aged ≥75 years. The number male and female patients are11 and 16 people. The mean duration of achieving the target INR at dose 2 mg, dose (2 mg and 4 mg) and dose 5 mg are 38.22, 29.33, and 6.56 days. There is a significant difference in the mean duration of achieving the target INR in the dose group. 5 mg dose had a mean duration of achieving the target INRwhich significantly different compared to the other doses.